2010
DOI: 10.1177/1091581809360282
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Capsinoids, XIII: Inhibitory Effects of Capsaicin and Capsinoids on Cytochrome P450 3A4 in Human Liver Microsomes

Abstract: This study evaluated potential effects of a number of capsinoids (ie, capsiate, dihydrocapsiate, nordihydrocapsiate) and a single capsaicinoid (ie, capsaicin) on liver microsomal cytochrome P450 3A4-mediated midazolam 1'-hydroxylase activity. Where possible, an inhibition curve was prepared; the concentration at which enzyme activity dropped to 50% was calculated. Capsaicin clearly inhibited cytochrome P450 3A4 activity, losing 50% of the activity at 21.5 micromol/L. No enzyme inhibition was observed in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…For instance, in vivo study showed that CAP strongly inhibited CYP3A4 activity, with the activity of the enzyme being 50% suppressed at the dosage of 21.5 micromol/L (Takanohashi et al, 2010). After treatment with high dose (3.0 mg/kg) CAP for 7 days, the P-gp and CYP3A1/2 in the liver and intestine were decreased at both the mRNA and protein levels, which would result in increased bioavailability of CYP3A-metabolized or P-gp-transported drugs (Zhai et al, 2013b).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, in vivo study showed that CAP strongly inhibited CYP3A4 activity, with the activity of the enzyme being 50% suppressed at the dosage of 21.5 micromol/L (Takanohashi et al, 2010). After treatment with high dose (3.0 mg/kg) CAP for 7 days, the P-gp and CYP3A1/2 in the liver and intestine were decreased at both the mRNA and protein levels, which would result in increased bioavailability of CYP3A-metabolized or P-gp-transported drugs (Zhai et al, 2013b).…”
Section: Introductionmentioning
confidence: 98%
“…There have been reported cases of unwanted pregnancies during the concomitant use of SJW and oral contraceptives [14,15]; however, raspberry ketone does not seem to reduce the efficacy of oral contraceptives. Capsaicin, which has a partially similar structural formula to raspberry ketone, reportedly has an inhibitory effect on CYP3A in vitro [16,17]. In a recent study, Zhai et al [18] reported that the blood concentration of cyclosporine A was significantly increased by capsaicin treatment and, conversely, the mRNA and protein levels of CYP3A and p-glycoprotein (p-gp) in the liver and intestine were decreased by capsaicin treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, on the other hand, CAP has attracted much more attention because of its additional abilities to modulate both cytochrome P450 monooxygenase isoform 3A (CYP3A) and ABC‐transporters. CAP was shown to be an inhibitor of CYP3A in in vitro studies . Moreover, there are several reports indicating that CAP exhibited inhibitory effects on P‐gp .…”
Section: Introductionmentioning
confidence: 99%